The Peace Puzzle : America's Quest for Arab-Israeli Peace, 1989-2011 - Kurtzer, Daniel (Book collections on Project MUSE., 2013)
In 2006, the authors of The Peace Puzzle formed the Study Group on Arab-Israeli Peacemaking, a project supported by the United States Institute of Peace, to develop a set of "best practices" for American diplomacy. The Study Group conducted in-depth interviews with more than 120 policymakers, diplomats, academics, and civil society figures and developed performance assessments of the various U.S. administrations of the post-Cold War period. This book, an objective account of the role of the United States in attempting to achieve a lasting Arab-Israeli peace, is informed by the authors' access to key individuals and official archives."--Pub. desc.